Synthesis, characterization, and catalytic activity of nitrogen and iron(III) co-doped TiO2 - Patsaya Songkhum (2018)
The nitrogen and iron(III) co-doped TiO2(N-Fe-TiO2) samples were synthesized via modified sol-gel method by using alkyl amine as both nitrogen source and pore directing agent. Morphologies and properties of the co-doped TiO2samples were investigated by X-ray diffraction, Fourier transform infrared spectroscopy, electron spin resonance spectroscopy, UV-Vis spectroscopy, scanning electron microscopy, and transmission electron microscopy. The results showed anatase phase mixed with rutile structure as well as hydroxyl and amine functional groups. The presence of Fe3+in N-Fe-TiO2sample was detected at g value of 2.00. In addition, the prepared samples were photocatalytically active for methyl orange degradation under UV light irradiation, but not under visible light. © 2012 Springer Science+Business Media B.V.